Diseño y propuesta para la implementación del Sistema de Gestión Integrado QHSE para la empresa CURVA LTDA de Villavicencio (2017)
The present document describes how it was carried out design and the proposal for implementation the integrated management system for the company CURVA LTDA of the city of Villavicencio, this project takes into account only two stages that are the planning and to Doing the IMS To start the process of designed of integrated management system in the company, it elaborated a check list in the that it determines the requirements to comply of each one of the norms ISO 9001:2015, ISO 14001:2105 y OHSAS 18001:2015:2007, with this information it is achieve to get an analysis of it is how in that it find the company and to determine that action to start to implement. In the pacification it was carried out an analysis the organizational context, determining the internal y external factors that affect to company, the stakeholders and identification and determination of strategic direction of the company, in the same way it was carried out a identification of the risks and opportunities in quality and environment topics, identification of the dangers and determination of controls and identification of legal requirements applicable in quality, environment and occupational health and safety. taking into account this information it was design a matrix of strategic direction in which it is relates the integral management politic, the integral objectives, indicators for measuring and monitoring, established goal and responsible of fulfillment. Of This way it is ensure that the objectives established are measurable and quantifiable for the achieve its scope. After this proceeded to design the quality management programs, environment management programs and occupational health and safety programs, profiles and function´s manual, once designed this documentation, it was elaborated a passbook where was invited all personal to be part of the implementation and certification of integrate management system and the important that is to the company keep this process and take hold more in the market with a good image and business projection. Also in the organization it was promoted the communication, participation and consult for the employees in which it is emphasized the importance that have the personal in the decisions that are made in the company in Quality, environment, occupation health and safety topics. Finally it was carried a job´s schedule where they present the activities that they was carried for To execute the process of to plan and to do to the present project.